PEMBUATAN DAN KARAKTERISASI SIFAT FISIKA GREEN CARBON PAPER TANPA PEREKAT MENGGUNAKAN LIMBAH BIOMASSA - E. Taer; Desmawati Desmawati; Sugianto Sugianto; R. Taslim (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Preparation and characterization of green carbon paper (GCP)without adhesive material using waste biomass has been successfully created. (GCP) made using biomass material from banana peels. GCP-The production of  GCP was begins with the grinding process with a time of 5 and 15 minutes. After grinding process followed by casting used  a container with an area of â€‹â€‹each 18 cm x 8 cm, 12 cm x 8 cm and 9 cm x 7 cm respectively. The next process is followed by a drying process at a temperature of 140o C for 24 hours. Characterization of physical properties are performed on samples GCP ware used Scanning electron microscopy (SEM) to determine the topology and surface morphology, energy dispersive X-ray (EDX) to determine the content of the element, and the X-ray diffraction to determine the degree of cristalinity. Measurements of weight, thickness and wide of sample GCP also perfomed to calculate density values. Based on dimention and weight measurements have been calculated the density value  for various milling of GCP  ware 0.825 g /cm3 and 0.698 g/cm3respectively. Characterization XRD showed GCP amorphous carbon is characterized by the presence of peaks at angles 2Î¸ = 23,936o and 48,939o. Based on SEM measurements indicated that the particles are the building blocks of the GCP in the form of aglomerate.Keywords : Green Carbon Paper, Banana Peel, Physical Properties.